Foreign exchange intervention in inflation targeters in Latin America - Chamon, Marcos,Hofman, David,Magud, Nicolas,Werner, Alejandro M. (International Monetary Fund, 2019)
Introduction : book in brief / Marcos Chamon, David Hofman, Nicolás E. Magud, and Alejandro Werner. Why intervene? / Marcos Chamon and NIcolás E. Magud – A taxonomy of intervention / Oscar A. Hendrick, Nicolás E. Magud, and Asad Qureshi – The effectiveness of intervention / Marcos Chamon, David Hofman, Sergi Lanau, Umang Rawat, and Miklos Vari – Forward intervention / Chris Walker – Intervention under inflation targeting / Marcos Chamon, David Hofman, Nicolás E. Magud, Umang Rawat, and Alejandro Werner – Brazil : taking stock of the past couple of decades / João Barata R. B. Barroso – Interventions in Chile / Catalina Larraín and Diego Saravia – Learning from experience in Colombia / Pamela Cardozo – Costa Rica : learning to float / Rodrigo Cubero, Valerie Lankester, and Evelyn Muñoz – Mexico : free-floating exchange regime / Rodrigo Cano, Daniela Gallardo, and Jaime Acosta – Peru : foreign exchange intervention under financial dollarization / Adrian Armas and Marco Vega – Uruguay : interventions and their effects / Elizabeth Bucacos, Alberto Graña, Gerardo Licandro, and Miguel Mello. Foreign exchange intervention is widely used as a policy tool, particularly in emerging markets, but our understanding of many facets of this tool remain limited, especially in the context of flexible exchange rate regimes. The Latin American experience shows how some of its largest countries have adopted floating exchange rate regimes and inflation targeting while continuing to intervene in foreign exchange markets
Includes bibliographical references and index
Keywords: Graue Literatur; Aufsatzsammlung; Wechselkurspolitik; Inflationssteuerung; Lateinamerika; Foreign exchange; Inflation (Finance); Inflation targeting; Währungspolitik; Geldpolitik; Inflation Targeting; Latin America